(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Prolonged mobile phone use has generated apprehensions about subtle auditory effects resulting from chronic unilateral exposure to radiofrequency electromagnetic fields (RF-EMF) and acoustic stimulation. Identifying early cochlear dysfunction prior to the manifestation of clinically significant hearing loss continues to be a public health imperative. This study sought to identify preclinical cochlear alterations by comparing hearing thresholds between the predominantly exposed ear and the contralateral ear in habitual mobile phone users. Methods: A cross-sectional observational study was performed. A pretested, structured questionnaire was given to all participants to collect data. Self-reported auditory complaints, such as tinnitus, ear discomfort, or perceived hearing difficulties, were collected within the questionnaire. Tympanometry and pure tone audiometry was conducted as a part of audiology testing. Paired t-test was used to compare the pure tone hearing thresholds of the exposed and unexposed ear. A p-value of less than 0.05 was considered to be statistically significant. Results: At higher and speech-related frequencies, the predominantly exposed ear exhibited significantly increased thresholds (p<0.05), indicating early cochlear stress, although the values remained within clinically normal limits. Correlation analysis revealed a weak yet statistically significant positive correlation between the duration of daily mobile phone usage and hearing thresholds in the predominantly exposed ear (Pearson’s r = 0.28, p = 0.006). Conclusion: The present study shows that the ear that is mostly exposed to mobile phones in medical students who use them frequently has much higher hearing thresholds than the ear that is not exposed to mobile phones.